Preparation method and application of responsive dynamic hydrogel

By constructing a dynamic hydrogel coating based on oxidized sodium alginate and chitosan derivatives on medical materials and devices, the problem of difficult, costly and lack of functionality in the prior art is solved, rapid gelling, pH, ROS response and appropriate elastic modulus are achieved, and biocompatibility and therapeutic effects are improved.

CN119564948AActive Publication Date: 2025-03-07NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH

Patent Information

Application Number
CN202411757887.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

It is difficult, costly and lacks functionality for the preparation of hydrogel coatings for existing medical materials and devices.

Method used

The aldehyde group of sodium oxidized alginate is used to form imine bond crosslinking with chitosan derivatives and aminophenylboric acid, and the phenylboric acid group of aminophenylboric acid is used to form borate ester bond crosslinking with chitosan, sodium oxidized alginate, and polyvinyl alcohol to prepare a dynamic hydrogel with rapid gelling ability, pH, ROS response and suitable elastic modulus.

Benefits of technology

The transient gelation, pH and ROS response of hydrogels are achieved, the preparation cost is reduced, the biocompatibility and therapeutic effect of medical materials are improved, and the application scenarios of hydrogel coatings are expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564948A_ABST
    Figure CN119564948A_ABST
Patent Text Reader

Abstract

The invention discloses a responsive dynamic hydrogel preparation method, which comprises: 1, dispersing sodium alginate, carrying out a directional oxidation reaction on the dispersed sodium alginate and a sodium periodate aqueous solution to obtain aldehyde group-containing oxidized sodium alginate, and dissolving the aldehyde group-containing oxidized sodium alginate in a hot solution of polyvinyl alcohol to obtain a precursor mother solution A; 2, dissolving a water-soluble chitosan derivative in deionized water, adding aminophenylboronic acid small molecules, and heating to obtain a precursor mother solution B; 3, uniformly mixing the precursor mother liquor A and the precursor mother liquor B to obtain dynamic hydrogel; the preparation method comprises the following steps: coating a precursor mother solution A on a medical material matrix, and then coating the precursor mother solution B on the medical material matrix. According to the invention, an aldehyde group and an amido group form imine bond cross-linking, and a phenylboronic acid group and vicinal diol form boric acid ester bond cross-linking, so that the prepared hydrogel has rapid gelling ability, pH and ROS responsiveness and proper elastic modulus; after the hydrogel disclosed by the invention is applied to a medical material matrix, the biological responsiveness and the interface mechanical softness of the medical material matrix are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical coatings, and in particular relates to a preparation method of a responsive dynamic hydrogel and an application thereof. Background Art

[0002] When biomedical materials are used in implantation or interventional treatment scenarios, they usually come into direct contact with human soft tissue. At present, common medical materials including metals, ceramics, polymers, etc. generally have adaptation differences with human soft tissue in terms of mechanical properties and other physical and chemical properties. This mismatch can easily induce a series of immune responses in the body, such as local inflammation and scar tissue formation. Taking vascular stents as an example, their hydrophobic surface often causes proteins and platelets to aggregate and adhere to the surface of the stent, which in turn causes restenosis of the blood vessels and even causes thrombosis, seriously affecting the treatment effect and the health and safety of patients.

[0003] As a type of solid-like material with high water content, hydrogel has unique soft mechanical properties and excellent biocompatibility. It has great application potential in the biomedical field and is a highly anticipated functional coating material. When constructing hydrogel coatings on medical material matrices, the three-dimensional network architecture formed by cross-linking has significant advantages, which not only facilitates the loading of various drugs and helps to achieve efficient drug loading, but also effectively optimizes the biological functionality of implantable materials. Among them, hydrogels constructed based on polymer networks formed by dynamic covalent cross-linking have unique performance. On the one hand, they exhibit shear-thinning properties under stress response, which facilitates deformation adaptation in different medical applications, and at the same time demonstrates the ability to respond to the stimulation of specific chemicals. Hydrogels cross-linked with borate bonds can produce network de-crosslinking behavior for glucose and reactive oxygen species (ROS), which meets the needs of local drug controlled release treatment for patients with diabetes and cancer. Hydrogels cross-linked with imine bonds are sensitive to pH changes and can release loaded drugs in local physiological weak acidic environments. In addition, given that dynamic covalent bonds have the advantages of both robustness and reversibility, when hydrogels constructed by their cross-linking are used as coatings for medical materials or medical devices, on the one hand, they can give the coatings appropriate mechanical strength and mechanical adaptability, ensuring that the coatings can function stably under complex stress conditions; on the other hand, their self-healing properties can effectively repair possible micro-damages to the coatings, greatly expanding the scope of practical application scenarios of the coatings and extending their service life; finally, the rapid cross-linking kinetics of dynamic covalent bonds are conducive to the rapid formation of hydrogel coatings, fully meeting the demands for rapid preparation, long-term, stable, and efficient use in biomedical scenarios.

[0004] Therefore, constructing a responsive hydrogel coating based on dynamic borate ester bonds and imine bond cross-linking on the surface of medical materials to optimize the mechanical adaptability of the material, enhance biocompatibility, and improve the hydrophilic-hydrophobic interface properties has become an extremely critical frontier development trend in the field of medical coating technology, which has far-reaching significance for improving the clinical application efficacy of biomedical materials and ensuring the diagnosis and treatment prognosis of patients. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a responsive dynamic hydrogel coating in view of the deficiencies of the above-mentioned prior art. The method uses the aldehyde group of oxidized sodium alginate to form an imine bond crosslink with the chitosan derivative and the amine group of aminophenylboronic acid, and at the same time, the phenylboronic acid group of aminophenylboronic acid forms a borate ester bond crosslink with the chitosan, oxidized sodium alginate, and the vicinal diol of polyvinyl alcohol, so that the prepared hydrogel has rapid gelation ability, pH, ROS responsiveness and suitable elastic modulus, which solves the problems of difficulty in preparing hydrogel coatings for existing medical materials and devices, high coating preparation cost and lack of coating functionality.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a responsive dynamic hydrogel, characterized in that the method comprises the following steps:

[0007] Step 1, preparation of hydrogel precursor mother solution A: sodium alginate is dispersed in anhydrous ethanol, and a sodium periodate aqueous solution is used for directed oxidation reaction under light-proof conditions. After the reaction is terminated, the oxidized sodium alginate containing aldehyde groups is obtained through purification, and then the oxidized sodium alginate containing aldehyde groups is dissolved in a hot solution of polyvinyl alcohol to obtain precursor mother solution A;

[0008] Step 2: Preparation of hydrogel precursor mother solution B: dissolving a water-soluble chitosan derivative in deionized water, then adding aminophenylboronic acid small molecules, and heating and stirring to react to obtain precursor mother solution B;

[0009] Step 3, preparation of hydrogel: the precursor mother solution A obtained in step 1 and the precursor mother solution B obtained in step 2 are rapidly stirred and mixed at a volume ratio of 1:1-2 to obtain a dynamic hydrogel with instantaneous gelation and pH and ROS responsiveness.

[0010] Typically, in step 1 of the present invention, sodium alginate is added to rapidly stirred anhydrous ethanol, and then an aqueous sodium periodate solution is added dropwise under light-proof conditions. After the dropwise addition is completed, a directional oxidation reaction is carried out by stirring at room temperature for 6 hours. After the reaction is completed, ethylene glycol is added to terminate the reaction, and stirring is continued at room temperature overnight. Finally, the suspension obtained by the reaction is transferred to a large amount of anhydrous ethanol under stirring, and the precipitate is collected by filtration. The precipitate is then dissolved in deionized water and dialyzed in deionized water, and finally freeze-dried to obtain oxidized sodium alginate containing aldehyde groups.

[0011] The aldehyde content in oxidized sodium alginate is determined by the hydroxylamine hydrochloride titration method described in patent application number 202311594957.9. Generally, the aldehyde content in oxidized sodium alginate is 6.5 mmol / g to 8.1 mmol / g.

[0012] The relative molecular weight of oxidized sodium alginate is measured by gel permeation chromatography (GPC). Generally, the average molecular weight of oxidized sodium alginate is 120 kDa to 154 kDa, and the molecular weight distribution (DPI) is 1.29 to 1.38.

[0013] The above-mentioned method for preparing a responsive dynamic hydrogel is characterized in that the concentration of sodium alginate dispersed in anhydrous ethanol in step 1 is 0.1 g / mL to 0.2 g / mL. Generally, heating magnetic stirring is used for dispersion, and the dispersion temperature is 40°C, and the dispersion time is 30 min to 60 min to obtain an anhydrous ethanol suspension of sodium alginate that is uniformly dispersed and free of block aggregation.

[0014] The above-mentioned method for preparing a responsive dynamic hydrogel is characterized in that the molar ratio of sodium periodate to sodium alginate monomer units in the sodium periodate aqueous solution in step 1 is 0.5:1 to 1.2:1.

[0015] The above-mentioned method for preparing a responsive dynamic hydrogel is characterized in that the method for terminating the reaction in step 1 is to add ethylene glycol, and the molar ratio of ethylene glycol to sodium periodate in the sodium periodate aqueous solution is 1.5:1 to 1.2:1.

[0016] The above-mentioned method for preparing a responsive dynamic hydrogel is characterized in that the purification method described in step 1 is: the reaction system solution is transferred dropwise to 2 to 3 times stirred anhydrous ethanol, and then the precipitate is collected by filtration, the precipitate is dissolved in deionized water and dialyzed in deionized water, and then freeze-dried. Usually, the precipitated white precipitate is collected by filtration, the precipitate is filtered and the solid precipitate is collected after multiple suction filtration, and then the solid precipitate is dissolved in deionized water, and after being loaded into a dialysis bag, it is placed in deionized water for 1 to 2 weeks, and then freeze-dried to obtain white cotton-like oxidized sodium alginate.

[0017] The above-mentioned method for preparing a responsive dynamic hydrogel is characterized in that the total polymer in the precursor mother solution A in step one includes oxidized sodium alginate containing aldehyde groups and polyvinyl alcohol, the concentration of which is 0.14 g / mL, the concentration of polyvinyl alcohol is 0.1 g / mL, and the mass ratio of oxidized sodium alginate containing aldehyde groups to polyvinyl alcohol is 5:2.

[0018] Typically, after polyvinyl alcohol is fully swollen in cold water, it is heated and stirred in a 95°C metal bath for 2 hours to obtain a transparent, uniform polyvinyl alcohol solution with a mass volume concentration of 10%; subsequently, oxidized sodium alginate containing an aldehyde group is added and stirred for 30 minutes while stirring in an 80°C metal bath to obtain a slightly yellow, translucent uniform solution, namely, precursor mother solution A.

[0019] The above-mentioned method for preparing a responsive dynamic hydrogel is characterized in that the water-soluble chitosan derivative in step 2 is carboxymethyl chitosan, carboxylated chitosan, chitosan quaternary ammonium salt, chitosan hydrochloride or chitosan lactate, and the concentration dissolved in deionized water is 0.02 g / mL; the aminophenylboronic acid small molecule is 2-aminophenylboronic acid, 3-aminophenylboronic acid or 4-aminophenylboronic acid, and the concentration after addition is 0.018 g / mL.

[0020] Typically, a water-soluble chitosan derivative is fully swollen in cold water, heated and stirred in a 50°C metal bath for 2 hours to obtain a transparent, uniform solution; then, aminophenylboronic acid small molecules are added and stirred for 2 hours while stirring in a 50°C metal bath, and the reaction is continued by stirring in a 60°C metal bath for 6 hours to obtain a transparent, uniform solution, namely, precursor mother solution B.

[0021] At the same time, the present invention also discloses an application of a responsive dynamic hydrogel prepared by the above method, characterized in that the precursor mother solution A obtained in step one is coated on a medical material matrix, and then the precursor mother solution B obtained in step two is coated on the precursor mother solution A, so as to obtain an instantaneous gelling, pH and ROS responsive dynamic hydrogel coating on the surface of the medical material.

[0022] The above application is characterized in that the coating method of the precursor mother solution A and the precursor mother solution B is derived from brushing, scraping, solution casting, dipping, spin coating, spraying, inkjet / 3D printing.

[0023] The above application is characterized in that the medical material matrix is ​​derived from metal titanium, magnesium, zinc, iron and their alloys, ceramic hydroxyapatite, polypropylene, polyvinyl chloride polymer medical materials and devices.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] 1. The present invention adopts aminophenylboronic acid small molecule phenylboronic acid and the vicinal diol of water-soluble chitosan derivative to form borate ester bond grafted on the chitosan derivative chain, and then mixed with oxidized sodium alginate and a hot solution of polyvinyl alcohol containing aldehyde groups, so that the aldehyde group of oxidized sodium alginate is cross-linked with the amine group of chitosan and grafted / ungrafted aminophenylboronic acid to form an imine bond network, and the ungrafted aminophenylboronic acid and the phenylboronic acid of the borate ester bond dynamically dissociated further rapidly form borate ester bond cross-linking with polyvinyl alcohol and the vicinal diol of oxidized sodium alginate. Under the action of the above-mentioned multiple cross-linking effects, rapid cross-linking is promoted to form an instantaneous hydrogel, thereby obtaining a dynamic hydrogel with instant gelation, pH and ROS responsiveness.

[0026] 2. The dynamic hydrogel prepared by the present invention is formed based on dynamic borate ester bonds and imine bonds cross-linked, can respond to ROS (reactive oxygen species) and pH, can be used for inflammatory and low pH treatment sites, and can be used for controlled release of loaded drugs, thereby improving the therapeutic effect of medical materials.

[0027] 3. The functional polymer for preparing the dynamic hydrogel of the present invention only needs to be synthesized by oxidizing sodium alginate, and the synthesis process is easy to implement and has low cost, thereby reducing the preparation cost of the dynamic hydrogel.

[0028] 4. The main polymers used to prepare the dynamic hydrogel in the present invention are sodium alginate and chitosan derivatives of biological origin, and polyvinyl alcohol with good biocompatibility, and all of them can achieve a certain degree of degradation under physiological conditions, which is beneficial for the dynamic hydrogel to be used as a coating for inert or degradable biomedical materials, thereby improving the biocompatibility and safety of the material matrix.

[0029] 5. The dynamic hydrogel coating of the present invention is formed by contacting two precursor mother solutions with different viscosities. Precursor mother solution A containing polyvinyl alcohol and sodium alginate oxide with high viscosity and good adhesion first adheres to the surface of the medical material substrate, and then the precursor mother solution B containing chitosan and aminophenylboronic acid with low viscosity spreads thereon and quickly gels with the precursor mother solution A to form a non-flowing hydrogel coating. The hydrogel is formed by instantaneous rapid cross-linking, which improves the preparation efficiency of constructing a hydrogel coating on the surface of the medical material, and can be applied to various coating processes such as brushing, scraping, solution casting, dipping, spin coating, spraying, inkjet / 3D printing, etc., and has a wide range of operation.

[0030] 6. The dynamic hydrogel coating of the present invention can adjust the dynamic mechanical properties and elastic modulus of the coating by adjusting the composition or concentration of the preparation mother solution, and exhibits adjustable shear thinning behavior. After the gel is formed, the coating can be constructed by injection, printing, etc. by applying shear force, and can realize the construction of complex and irregular hydrogel coatings for various medical materials or devices.

[0031] 7. The dynamic hydrogel prepared by the present invention is formed based on reversible dynamic borate ester bonds and imine bonds cross-linked, and exhibits certain self-healing properties, which is beneficial for the self-repair of the coating when it is damaged by external stress, and plays an important role in extending the service life of the hydrogel coating.

[0032] 8. The dynamic hydrogel coating of the present invention can be prepared on various medical materials or device substrates, has a wide range of applications, and the coating preparation method has strong operability and good repeatability, and has good application prospects in the medical industry.

[0033] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is the Fourier infrared spectra of sodium alginate and oxidized sodium alginate in Invention Example 1.

[0035] Figure 2 This is the gel-dissolution transition diagram of the pH and ROS responses of the dynamic hydrogel prepared in Example 2 of the present invention.

[0036] Figure 3 This is a frequency scanning result diagram of the rheological test of the dynamic hydrogel prepared in Example 2 and Example 4 of the present invention.

[0037] Figure 4 This is a graph showing the strain scanning results of the rheological test of the dynamic hydrogels prepared in Examples 2 and 4 of the present invention.

[0038] Figure 5 The survival rate of NIN / 3T3 cells after being treated with the dynamic hydrogel prepared in Examples 1 to 3 of the present invention for 48 hours.

[0039] Figure 6 These are SEM images of the dynamic hydrogels prepared in Examples 1 to 3 of the present invention.

[0040] Figure 7 This is a schematic diagram of the process of applying the responsive dynamic hydrogel of the present invention to the surface coating of medical materials.

[0041] Figure 8 This is a SEM image of the surface of the magnesium alloy WE43 disc after alkali heat treatment in Example 15 of the present invention.

[0042] Fig. 9 This is a SEM image of the magnesium alloy WE43 disc after a dynamic hydrogel coating is formed on the surface of the disc in Example 15 of the present invention.

[0043] Fig.10 These are the contact angle test results of the magnesium alloy WE43 disc surfaces after alkaline heat treatment and the formation of dynamic hydrogel coatings in Examples 13, 14 and 15 of the present invention. DETAILED DESCRIPTION

[0044] The preparation method of the responsive dynamic hydrogel of the present invention is described in detail through Examples 1 to 12.

[0045] Example 1

[0046] This embodiment includes the following steps:

[0047] Step 1, preparation of hydrogel precursor mother solution A: 20g sodium alginate was dispersed in 100mL anhydrous ethanol and stirred in a 40°C water bath for 60min to obtain a uniformly dispersed turbid solution, 100mL of 0.108g / mL sodium periodate aqueous solution was added dropwise to the turbid solution under dark conditions, the molar ratio of sodium periodate to sodium alginate monomer unit was 0.5:1, after the addition was completed, the directional oxidation reaction was continued to be stirred at room temperature in the dark for 6h, after the reaction was completed, 4.7g ethylene glycol was added to terminate the reaction, the molar ratio of ethylene glycol to sodium periodate in the sodium periodate aqueous solution was 1.5:1, and stirred at room temperature overnight, and the reaction system solution was transferred dropwise to 6 00mL of anhydrous ethanol in a stirring state, and then filter and collect the precipitate, dissolve the precipitate in deionized water and put it into a dialysis bag (MWCO: 8000Da~14000Da), dialyze in deionized water for 2 weeks, and then freeze-dry to obtain oxidized sodium alginate containing aldehyde groups. After testing, the aldehyde group concentration of the oxidized sodium alginate is 6.5mmol / g, the number average molecular weight is 154kDa, and the molecular weight distribution DPI is 1.29; 0.2g of the oxidized sodium alginate containing aldehyde groups is dissolved in 5mL of a polyvinyl alcohol aqueous solution with a mass volume concentration of 10% in a metal bath at 80°C under stirring, and stirred for 30min to obtain a precursor mother solution A;

[0048] Step 2, preparation of hydrogel precursor mother solution B: dissolve 0.1g carboxymethyl chitosan in 5mL deionized water, fully swell for 0.5h, stir at 50°C for 2h to promote dissolution, then add 0.09g 3-aminophenylboronic acid, continue stirring at 50°C for 2h, and then stir at 60°C for 6h. Seal or protect with nitrogen during the stirring process to obtain precursor mother solution B;

[0049] Step 3. Preparation of hydrogel: The precursor solution A obtained in step 1 and the precursor solution B obtained in step 2 were rapidly stirred and mixed at a volume ratio of 1:1 to obtain a dynamic hydrogel with instantaneous gelation, pH and ROS responsiveness, recorded as BG1.

[0050] The 3-aminophenylboronic acid in this embodiment can also be replaced by 2-aminophenylboronic acid or 4-aminophenylboronic acid.

[0051] Example 2

[0052] The difference between this embodiment and embodiment 1 is that the water-soluble chitosan derivative of the hydrogel coating precursor mother solution B prepared in step 2 is carboxylated chitosan, and a dynamic hydrogel with instant gelation, pH and ROS responsiveness is obtained, which is recorded as BG2.

[0053] Example 3

[0054] The difference between this embodiment and embodiment 1 is that the water-soluble chitosan derivative of the hydrogel coating precursor mother solution B prepared in step 2 is chitosan quaternary ammonium salt, and a dynamic hydrogel with instant gelation, pH and ROS responsiveness is obtained, which is recorded as BG3.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that in step 3, the volume ratio of precursor solution A to precursor solution B for preparing the hydrogel coating is 1:2, and a dynamic hydrogel with instantaneous gelation, pH and ROS responsiveness is obtained, which is recorded as BG4.

[0057] Example 5

[0058] The difference between this embodiment and embodiment 2 is that the volume ratio of the precursor mother solution A to the precursor mother solution B for preparing the hydrogel coating in step 3 is 1:2.

[0059] Example 6

[0060] The difference between this embodiment and embodiment 3 is that the volume ratio of the precursor mother solution A to the precursor mother solution B for preparing the hydrogel coating in step 3 is 1:2.

[0061] Example 7

[0062] The difference between this embodiment and embodiment 1 is that: in step 1, the concentration of sodium alginate dispersed in anhydrous ethanol is 0.1 g / mL, the stirring time of dispersion is 30 min, the molar ratio of the added sodium periodate to the sodium alginate monomer unit is 1.2:1, and the molar ratio of the added ethylene glycol to the sodium periodate is 1.2:1; the reaction system solution is transferred dropwise into 2 times the volume of anhydrous ethanol in a stirring state, and the oxidized sodium alginate obtained has an aldehyde group concentration of 8.1 mmol / g, a number average molecular weight of 120 kDa, and a molecular weight distribution DPI of 1.38.

[0063] Example 8

[0064] The difference between this embodiment and embodiment 7 is that the water-soluble chitosan derivative used in preparing the hydrogel coating precursor mother solution B in step 2 is carboxylated chitosan, and a dynamic hydrogel with instant gelation, pH and ROS responsiveness is obtained.

[0065] Example 9

[0066] The difference between this embodiment and embodiment 7 is that the water-soluble chitosan derivative in the preparation of the hydrogel coating precursor mother solution B in step 2 is chitosan quaternary ammonium salt, and a dynamic hydrogel with instant gelation, pH and ROS responsiveness is obtained.

[0067] Example 10

[0068] The difference between this embodiment and embodiment 7 is that in step 3, the volume ratio of precursor solution A to precursor solution B for preparing the hydrogel coating is 1:2, and a dynamic hydrogel with instant gelation, pH and ROS responsiveness is obtained.

[0069] Embodiment 11

[0070] The difference between this embodiment and embodiment 8 is that in step 3, the volume ratio of precursor mother solution A to precursor mother solution B for preparing the hydrogel coating is 1:2.

[0071] Example 12

[0072] The difference between this embodiment and embodiment 9 is that in step 3, the volume ratio of precursor solution A to precursor solution B for preparing the hydrogel coating is 1:2.

[0073] (I) FTIR characterization

[0074] The sodium alginate and oxidized sodium alginate of Example 1 of the present invention were characterized by Fourier transform infrared spectroscopy (FTIR). The specific process was as follows: all samples were freeze-dried and then uniformly mixed with KBr dried to constant weight at a mass ratio of 1:100, ground with an agate mortar, pressed into tablets, and placed in a Fourier transform infrared spectrometer for test scanning, with a scanning range of 400 cm -1 ~4000cm -1 , the results are as follows Figure 1 shown.

[0075] from Figure 1 It can be seen that sodium alginate and oxidized sodium alginate have a range of 3270-3220 cm -1 、2920cm -1 、1594cm -1 The characteristic peaks at the positions correspond to the stretching vibration peaks of OH, CH, -COO and - The asymmetric stretching vibration peaks of sodium alginate indicate that after directional oxidation with sodium periodate, oxidized sodium alginate still retains the main functional groups of sodium alginate, such as hydroxyl and carboxyl. At the same time, the characteristic peak of hydroxyl (OH) of oxidized sodium alginate is slightly red-shifted and weakened compared with that of sodium alginate, and the peak of oxidized sodium alginate at 1730cm -1New characteristic absorption peaks appeared at 880cm-1, corresponding to the stretching vibration peaks of aldehyde groups (C=O), indicating that oxidized sodium alginate has fewer hydroxyl groups and newly appeared aldehyde groups than sodium alginate, which is also consistent with the reaction mechanism that the vicinal diol of sodium alginate is converted into aldehyde groups after directional oxidation. -1 The characteristic absorption peak at corresponds to the stretching vibration of COC of the glycosidic bond. This absorption peak becomes less obvious in oxidized sodium alginate, which may be due to the partial breakage of the glycosidic bond of sodium alginate caused by nonspecific oxidative cleavage under the action of NaIO4 and the overlap of the characteristic peaks of the hemiacetal structure formed by the condensation reaction of the aldehyde group of oxidized sodium alginate and some dihydroxyl groups. In summary, by comparing the FTIR test results of sodium alginate and oxidized sodium alginate, it is shown that some hydroxyl groups of sodium alginate are indeed converted into aldehyde groups through directional oxidation, confirming the successful aldehyde functionalization of oxidized sodium alginate.

[0076] (II) Self-healing performance

[0077] The formed hydrogel was cut into gel fragments using a utility knife, and the gel fragments were brought into contact with each other at the incision. After a period of time, one of the gel fragments was picked up with tweezers, and it was observed that the gel fragment did not fall from the incision under the action of gravity, indicating that the hydrogel had self-healing ability. After testing, the sample fragments of the hydrogel prepared in Examples 1 to 4 of the present invention were reassembled together for less than 1 minute, and the tweezers did not fall off, indicating that the dynamic hydrogel prepared by the present invention has good self-healing efficiency, which is beneficial to prolonging the service life of the hydrogel in practical applications and has a good covering effect on the medical material matrix.

[0078] (III) Stimulus responsiveness

[0079] The dynamic polymer network of the dynamic hydrogel based on the present invention is mainly cross-linked by dynamic borate bonds and imine bonds, so the breakage of any dynamic covalent bond will cause partial dissociation of the gel network. 20 μL of hydrogen peroxide with a mass concentration of 2.5% to 3.5% was added to the 200 μL dynamic hydrogel sample prepared in Example 2 of the present invention. After 5 hours, the hydrogel became significantly softer than the initial state, indicating that the active oxygen in the hydrogen peroxide caused the breakage of the borate bond. Subsequently, a 1M hydrochloric acid solution was used to adjust the pH of the gel to about 1 to 2. After 2 days, the hydrogel changed from a gel state to a sol state, as shown in FIG. Figure 2As shown. It shows that the dynamic hydrogel of the present invention can slowly dissociate the gel network in an acidic environment until it completely disintegrates. The experimental phenomenon also shows that the main driving force for the formation of the gel in this system may come from the imine bond, and the borate bond is also involved in the construction of the gel network. Therefore, the dynamic hydrogel of the present invention can be suitable for environments that respond to ROS, such as inflammation, and for acidic environments that respond to low pH, such as bacterial metabolism, and can be used for surface functional coatings of implanted or intervened medical materials to control the release of anti-inflammatory, antibacterial and other drugs, thereby enhancing the therapeutic effect of medical materials.

[0080] (IV) Rheological test

[0081] The hydrogel samples prepared in Example 2 and Example 4 of the present invention were subjected to rheological tests, mainly including rheological frequency scanning and strain scanning, to examine the oscillatory mechanical properties of the dynamic hydrogel samples.

[0082] The rheological test frequency scanning results of the dynamic hydrogel samples prepared in Example 2 and Example 4 of the present invention are as follows: Figure 3 The strain sweep results of the rheological test are shown in Figure 4 As shown. Figure 3 It can be seen that within the entire test frequency range, the storage modulus (G′) of the prepared dynamic hydrogel is always higher than the loss modulus (G″), indicating that these instantaneously formed dynamic hydrogels based on dynamic borate bonds and imine bonds have good rheological stability. At the same time, the storage modulus of the BG4 dynamic hydrogel in Example 4 is slightly higher than that of the BG2 dynamic hydrogel, indicating that under the premise of the same aldehyde concentration, increasing the content of the amino and boric acid groups alone will not have a significant effect on the elastic modulus of the dynamic hydrogel. The platform elastic modulus of the two hydrogels (BG2: 10200Pa, BG4: 11600Pa) is also much lower than that of most current medical materials. As a coating, it can effectively reduce the softness of its interface, reduce the stress damage of medical materials and devices to human soft tissues, and have a good protective and therapeutic effect on patients.

[0083] The strain scanning results of the rheological test of the dynamic hydrogels prepared in Example 2 and Example 4 of the present invention are as follows: Figure 4 As shown, it can be seen that the prepared dynamic hydrogel has the ability of shear thinning, which meets the basic characteristics of dynamic bond cross-linked gel, indicating that these dynamic hydrogels are expected to have the ability to be injected and printed under the action of shear force, and for hydrogels as coatings of medical materials, they will show better advantages in processing. Moreover, the shear strain and rupture strain of the BG4 dynamic hydrogel, which only increases the content of amine and boric acid groups, are significantly lower than those of the BG2 dynamic hydrogel, indicating that the shear thinning degree of these dynamic hydrogels can be regulated by adjusting the proportion of the precursor mother liquor, which provides a larger regulatory space for the processing and application of hydrogels as coatings of medical materials.

[0084] (V) Biocompatibility of hydrogel coating

[0085] Mouse embryonic fibroblasts (NIH / 3T3) were used to evaluate the cytotoxicity of the dynamic hydrogels BG1, BG2 and BG3 of Examples 1 to 3 of the present invention. The specific process was as follows: cells were inoculated in a 48-well plate at a cell density of 2×10 4 After 24 hours, the cells were observed to be attached to the wall and in good condition. Different volumes of dynamic hydrogel samples were placed in a 48-well plate, and 200 μL of DMEM complete medium was added to the well plate. The volume ratio concentration of each dynamic hydrogel sample to the medium was 15.625, 31.25, 62.5, and 125 (μL / mL), respectively. The medium without dynamic hydrogel samples was used as the control group. After culturing for 24h / 48h, 200 μL of medium containing 10% CCK-8 reagent was added to each well. After incubation in a 37°C incubator for 1h, the absorbance value at 450nm was detected using an enzyme reader to calculate the cell survival rate. The cytotoxicity test results after 48h are as follows: Figure 5 shown.

[0086] from Figure 5 It can be seen that with the increase of the volume concentration of the dynamic hydrogel sample, the toxicity of the hydrogel to cells increases, especially at high concentrations, the three gels BG1, BG2 and BG3 show obvious toxicity differences due to the different chitosan derivatives. At a low concentration of 15.625 (μL / mL), there is no obvious difference in toxicity among the three hydrogels, and the cell survival rate is comparable to that of the blank control group, indicating that these dynamic hydrogels have good biocompatibility and can effectively improve the biocompatibility of medical materials and device substrates as coatings.

[0087] (VI) SEM observation

[0088] After the dynamic hydrogel sample that had been freeze-dried was sprayed with gold on its surface, the surface morphology was observed using a scanning electron microscope (SEM).

[0089] Figure 6The SEM images of the dynamic hydrogels prepared in Examples 1 to 3 of the present invention. As can be seen from the figure, the gel network pore sizes of the dynamic hydrogels BG1, BG2 and BG3 prepared in Examples 1 to 3 are different. This shows that under the premise of the same component concentration, the network structure inside the hydrogel can be easily regulated by only changing the type of chitosan derivative. The microscopic network structure of the gel can affect the mechanical properties of the gel. Therefore, according to the needs of medical materials in different application scenarios, dynamic hydrogels with suitable mechanical properties can be prepared by changing the type of chitosan derivatives. At the same time, the rich multi-scale network structure is also conducive to the loading of drug molecules and micro-nano materials, which makes it possible for dynamic hydrogels to load specific biological functional substances as medical materials, and is conducive to realizing the biological functionality of hydrogel coatings of medical materials.

[0090] The application of the responsive dynamic hydrogel of the present invention is described in detail through Examples 13 to 24.

[0091] Embodiment 13

[0092] like Figure 7 As shown, this embodiment includes the following steps:

[0093] Step 1: After the magnesium alloy WE43 disc (diameter × thickness is Φ8mm × 3mm) is graded polished with 400-2000 mesh sandpaper, ultrasonic cleaning is performed for 15 minutes using acetone, deionized water, and anhydrous ethanol respectively. The cleaning process is repeated three times. After drying, it is placed in a 0.01M NaOH solution in a reactor, and alkaline heat treatment is performed in a 120°C oven for 12 hours. Finally, it is ultrasonically cleaned with deionized water and ethanol for 5 minutes, and then dried with nitrogen and stored in a vacuum for standby use;

[0094] Step 2: Place the WE43 disc reserved in step 1 as a substrate in a spin coater, first spin coat 100 μL of the precursor solution A prepared in step 1 in Example 1 of the present invention on the surface of the WE43 disc, and then coat the precursor solution B obtained in step 2 of the present invention on the precursor solution A, thereby constructing a dynamic hydrogel coating with instantaneous gelation, pH and ROS responsiveness on the surface of the medical degradable metal material WE43.

[0095] The WE43 wafer in this embodiment can also be replaced by other medical material matrices derived from metallic titanium, magnesium, zinc, iron and their alloys, ceramic hydroxyapatite, polypropylene, polyvinyl chloride polymer medical materials and devices, wherein alkaline heat treatment of the medical material matrix before coating the two precursor mother solutions is not a necessary step, and alkaline heat treatment is only for active metals such as Mg, Zn and their alloy materials.

[0096] The spin coating method in this embodiment can also be replaced by brushing, scraping, solution casting, dipping, spraying, inkjet / 3D printing and the like. The basic order is to first apply precursor solution A and then apply precursor solution B.

[0097] Embodiment 14

[0098] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 2 of the present invention and the precursor solution B in step 2 of embodiment 2 of the present invention, as well as the volume ratio in step 3 of embodiment 2.

[0099] Embodiment 15

[0100] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 3 of the present invention and the precursor solution B in step 2 of embodiment 3 of the present invention, as well as the volume ratio in step 3 of embodiment 3.

[0101] The freeze-dried sample of the magnesium alloy WE43 disc of Example 15 of the present invention after alkali heat treatment and covered with the dynamic hydrogel coating was observed by SEM. The results are as follows: Figure 8 and Fig. 9 As shown. Figure 8 It can be seen that after the magnesium alloy WE43 disc is subjected to the alkaline heat treatment of this embodiment, the surface of the WE43 disc is covered with a uniform and dense micro-nano flower structure; the roughness of the structure is conducive to forming a mechanical interlocking structure with the precursor mother liquid A, increasing the friction and bonding ability between the hydrogel coating and the WE43 disc substrate after formation, making the coating more firmly attached. Fig. 9 It can be seen that in the WE43 wafer Figure 8 After the BG3 hydrogel coating of Example 3 was formed on the micro-nanostructure shown in FIG. 1 , the microscopic network structure of the hydrogel coating did not change due to the carboxyl groups, hydroxyl groups, etc. in the gel that may interact with Mg. 2+ The bonded groups undergo significant changes, which proves that the hydrogel coating has good structural stability and further illustrates that the dynamic hydrogel coating designed by the present invention is also suitable for surface coating of active medical materials.

[0102] (VII) Contact angle test

[0103] The contact angle test was performed on the magnesium alloy WE43 discs of Examples 13 to 15 of the present invention, the surface of the WE43 disc after alkali heat treatment, and the surface covered with the hydrogel coating after alkali heat treatment to evaluate their hydrophilicity and hydrophobicity. 5 μL of deionized water was squeezed out from the syringe of the contact angle measuring instrument, and the needle was slowly moved down until the droplet touched the surface of the sample to be tested. The photo of the droplet on the surface and the wetting angle were recorded at 100 seconds. Fig.10As shown, the contact angle of the untreated magnesium alloy WE43 disc surface is 96°, showing obvious hydrophobicity; after the WE43 disc is treated by the alkali-heat method of Examples 13 to 15 of the present invention, the contact angle decreases to 63°, which is particularly conducive to the spreading of the precursor mother solution A thereon; then, as Fig.10 As shown in the figure, after the hydrogel coating is formed on the surface treated by alkali-heat method, the chitosan derivatives show different hydrophilic and hydrophobic properties due to different contact angles, which may be related to the hydrophobic properties of chitosan and aminophenylboronic acid after the formation of borate bond grafting. Nevertheless, the hydrophilicity of the hydrogel coating can still be adjusted by regulating the type of water-soluble chitosan. For example, the contact angle of the hydrogel coating constructed by BG3 is as low as 40°, showing good hydrophilicity, which has high practical value for improving the hydrophilicity and biocompatibility of the surface of medical materials.

[0104] Example 16

[0105] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 4 of the present invention and the precursor solution B in step 2 of embodiment 4 of the present invention, as well as the specific volume ratio in step 3 of embodiment 4.

[0106] Embodiment 17

[0107] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 5 of the present invention and the precursor solution B in step 2 of embodiment 5 of the present invention, as well as the specific volume ratio in step 3 of embodiment 5.

[0108] Embodiment 18

[0109] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 6 of the present invention and the precursor solution B in step 2 of embodiment 6 of the present invention, as well as the specific volume ratio in step 3 of embodiment 6.

[0110] Embodiment 19

[0111] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 7 of the present invention and the precursor solution B in step 2 of embodiment 7 of the present invention, as well as the specific volume ratio in step 3 of embodiment 7.

[0112] Embodiment 20

[0113] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 8 of the present invention and the precursor solution B in step 2 of embodiment 8 of the present invention, as well as the specific volume ratio in step 3 of embodiment 8.

[0114] Embodiment 21

[0115] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 9 of the present invention and the precursor solution B in step 2 of embodiment 9 of the present invention, as well as the specific volume ratio in step 3 of embodiment 9.

[0116] Embodiment 22

[0117] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 10 of the present invention and the precursor solution B in step 2 of embodiment 10 of the present invention, as well as the specific volume ratio in step 3 of embodiment 10.

[0118] Embodiment 23

[0119] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 11 of the present invention and the precursor solution B in step 2 of embodiment 11 of the present invention, as well as the specific volume ratio in step 3 of embodiment 11.

[0120] Embodiment 24

[0121] The difference between this embodiment and embodiment 13 is that the dynamic hydrogel coating is prepared by using the precursor solution A in step 1 of embodiment 12 of the present invention and the precursor solution B in step 2 of embodiment 12 of the present invention, as well as the specific volume ratio in step 3 of embodiment 12.

[0122] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a responsive dynamic hydrogel, characterized in that: The method comprises the following steps: Step 1, preparation of hydrogel precursor mother solution A: sodium alginate is dispersed in anhydrous ethanol, and a sodium periodate aqueous solution is used for directed oxidation reaction under light-proof conditions. After the reaction is terminated, the oxidized sodium alginate containing aldehyde groups is obtained through purification, and then the oxidized sodium alginate containing aldehyde groups is dissolved in a hot solution of polyvinyl alcohol to obtain precursor mother solution A; Step 2: Preparation of hydrogel precursor mother solution B: dissolving a water-soluble chitosan derivative in deionized water, then adding aminophenylboronic acid small molecules, and heating and stirring to react to obtain precursor mother solution B; Step 3, preparation of hydrogel: the precursor mother solution A obtained in step 1 and the precursor mother solution B obtained in step 2 are rapidly stirred and mixed at a volume ratio of 1:1-2 to obtain a dynamic hydrogel with instantaneous gelation and pH and ROS responsiveness.

2. The method for preparing a responsive dynamic hydrogel according to claim 1, characterized in that: The concentration of sodium alginate dispersed in anhydrous ethanol in step 1 is 0.1 g / mL to 0.2 g / mL.

3. The method for preparing a responsive dynamic hydrogel according to claim 1, characterized in that: The molar ratio of sodium periodate to sodium alginate monomer units in the sodium periodate aqueous solution in step 1 is 0.5:1 to 1.2:

1.

4. The method for preparing a responsive dynamic hydrogel according to claim 1, characterized in that: The method for terminating the reaction in step 1 is to add ethylene glycol, and the molar ratio of ethylene glycol to sodium periodate in the sodium periodate aqueous solution is 1.5:1 to 1.2:

1.

5. The method for preparing a responsive dynamic hydrogel according to claim 1, characterized in that: The purification method described in step 1 is: transferring the reaction system solution dropwise into 2-3 times stirred anhydrous ethanol, then filtering and collecting the precipitate, dissolving the precipitate in deionized water and dialyzing it in deionized water, and then freeze-drying it.

6. The method for preparing a responsive dynamic hydrogel according to claim 1, characterized in that: The total polymer in the precursor mother solution A in step 1 includes oxidized sodium alginate containing aldehyde groups and polyvinyl alcohol, the concentration of which is 0.14 g / mL, the concentration of which is 0.1 g / mL, and the mass ratio of oxidized sodium alginate containing aldehyde groups to polyvinyl alcohol is 5:

2.

7. The method for preparing a responsive dynamic hydrogel according to claim 1, characterized in that: The water-soluble chitosan derivative in step 2 is carboxymethyl chitosan, carboxylated chitosan, chitosan quaternary ammonium salt, chitosan hydrochloride or chitosan lactate, and the concentration dissolved in deionized water is 0.02 g / mL; the aminophenylboronic acid small molecule is 2-aminophenylboronic acid, 3-aminophenylboronic acid or 4-aminophenylboronic acid, and the concentration after addition is 0.018 g / mL.

8. Use of a responsive dynamic hydrogel prepared by the method according to any one of claims 1 to 7, characterized in that: The precursor solution A obtained in step one is coated on a medical material substrate, and then the precursor solution B obtained in step two is coated on the precursor solution A to obtain a dynamic hydrogel coating that is instantaneously gelled and responsive to pH and ROS on the surface of the medical material.

9. The use according to claim 8, characterized in that: The coating method of the precursor mother solution A and the precursor mother solution B is derived from brushing, scraping, solution casting, dipping, spin coating, spraying, inkjet / 3D printing.

10. The use according to claim 8, characterized in that: The medical material matrix is ​​derived from metal titanium, magnesium, zinc, iron and alloys thereof, ceramic hydroxyapatite, polypropylene, polyvinyl chloride polymer medical materials and devices.

Citation Information

Patent Citations

  • Preparation method and coating application of self-healing and antibacterial dynamic hydrogel

    CN117618643A

  • Carboxyethyl chitosan / polyvinyl alcohol self-healing hydrogel as well as preparation method and application thereof

    CN109517193A

  • Self-healing hydrogel with double dynamic networks and preparation method of hydrogel

    CN109575269A

  • Microenvironment-responsive multifunctional injectable hydrogel as well as preparation method and application thereof

    CN116785228A

  • Rhein-loaded double-dynamic cross-linked polysaccharide-based hydrogel and preparation method thereof

    CN118286150A

Cited By

  • Antibacterial hydrogel, antipyretic patch containing same and preparation process of antipyretic patch

    CN121421945A